Utilização de bactérias isoladas do solo para produção de xilanase e de bioetanol - Rodrigues, Isabela da Silva Vasconcelos (2019)
Microorganisms can secrete enzyme-rich substances that are capable of breaking down a series of organic molecules. Therefore, microorganisms have wide applicability in a number of biotechnological processes. Among the microbial enzymes, xylanases have high biotechnological potential and are of interest for the food, pharmaceutical and papermaking industries. Aside from the production of industrially useful enzymes, another trend of a biotechnological use of microorganisms is bioethanol production. This study addressed the isolation of soil bacteria for xylanase and bioethanol production. For xylanase production by Bacillus sp TC-DT13, agro-industrial residues were selected by submerged fermentation. The selected residue was used to produce xylanolytic enzymes by solid state fermentation. Of the tested residues, wheat bran was found to be the best inducer of xylanase production (1500 U/mL). On the other hand, wheat bran as the sole fermentation substrate in solid state fermentation for 144 hours, at a bran : moisture ratio of 1:4, induced an excessive amount of xylanase (2943 U/g). The use of carbon and nitrogen sources did not raise the xylanolytic enzyme production. The use of agro-industrial wastes in solid state fermentation, apart from increasing xylanase production and reducing costs, is also an environmentally friendly alternative. For ethanol production, Bacillus spp. and Paenibacillus sp were tested with regard to their ability to ferment xylose. The strains were subjected to xylose fermentation at different enzymatic concentrations. Among the strains tested for development evaluation in xylose medium, the five (TC-DT8, TC-DT64, TC-DT81 and TC-DT139 and TC-DT13) with highest cell growth in 2% xylose were selected. Under stirred fermentation, the ethanol production of the strains varied from 1.59 - 2.6 g L-1 . Therefore, it can be concluded that some of the bacterial strains tested were able to grow in xylose-containing medium. Moreover, Bacillus sp. TC-DT13 and Paenibacillus sp. TC-DT8 produced ethanol with and without stirring.